Market Liberalization and Performance of Oil Palm Smallholder Farmer’s Household - Andi Irawan (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2020)
This study aimed to analyze the impact of market The data used in the study are cross-section primary data related to the household economy of oil palm smallholder farmers. Data collection was carried out in three provinces of production center of oil palm in Indonesia i.e. Jambi, Sumatera Selatan, and Bengkulu. One district of oil palm production center is chosen for each province i.e. Muaro Jambi, Banyu Asin, and Bengkulu Utara, respectively. Total samples in this research are 155 farm households by using simple random sampling method, consist of 52 samples for Bengkulu Utara, 57 samples for Sumatera Selatan and 46 samples for Jambi, respectively. Primary data are collected from farmer household samples by survey method using questionnaires. The smallholder farmer’s oil palm household economic model in this study was formulated in a system of simultaneous equations. The results indicated that liberalization of the output market but still gave protection in the input market at least subsidized fertilizer will contribute positively not only to farming performance i.e. farm production and investment but also to farmer household welfare i.e. increased farming profit and consumption of basic need commodities and other goods which bought in the market.